Raspar a cabeça não altera a velocidade na corrida de 10 km sob o sol - Angelo Ruediger Pisani Martini (2009)
In a previous study conducted in our laboratory, we observed a physiological strain index (PSI), higher on individuals with scraped hair than individuals with hair, when they exercised in a treadmill with fixed workload under the sun. Therefore the purpose of the present study was to test if the human hair could be a natural protection against the sun radiation, allowing higher velocity during running under thesun. Participated in this study 12 healthy male volunteers capable of practicing exercise (29.5 ± 3.7 years old; height, 174.9 ± 4.3 cm; weight, 72.7 ± 3.2 kg and VO2max, 44.6 ± 3.4 ml.kg-1.min-1). They should have a have a hair al least 6 cm long. They came to the laboratory for 4 moments. On the first day anthropometric measurements and aerobic capacity test were accomplished. Two days later, they participed of the other three conditions: familiarization and 2 experimental conditions, intact hair and scraped hair, in this order. The volunteers had to run 10kmin 2 different days with at least one week apart. Every situation was done in a 200m planned grassy circuit. The environmental heat stress was measured by the Index of Wet Bulb Globe Temperature (WBGT) in oC. There was no diference between the conditions (24.0 ± 1.4 e 23.2 ± 1.5, for human hair and scraped hair respectively). The running velocity, heart rate, rectal temperature, physiological index stress and rate of heat storage were measured. The result showed that the running velocity(10,9 ± 1 e 10,9 ± 1,1 km.h-1), heart rate (183 ± 10 e 180 ± 12 bpm), rectal temperature (38,82 ± 0,29 e 38,81 ± 0,49 oC), physiological index stress (9 ± 1 e 9 ± 1) and rate of heat storage (71,9 ± 64,1 e 80,7 ± 56,7 W.m-1), were not different in both situations. In conclusion, scraped hair does not change the velocity in a 10km running under the sun.